Electroacupuncture versus Escitalopram for mild to moderate Post-Stroke Depression: A randomized non-inferiority trial - Ma, Feixiang; Cao, Guiping; Lu, Lu; Zhu, Yingling; Li, Wanlang; Chen, Li (Frontiers in Psychiatry, 2024)
Objective: To explore the efficacy of electroacupuncture in treating post-stroke depression (PSD) by modulating the inflammatory response. Methods: One hundred and fifty participants with mild or moderate PSD were randomly divided into 75 cases each in the electroacupuncture group (EA group) and escitalopram group (ESC group). In the EA group, 30 sessions of electroacupuncture were performed on the Baihui, Yintang, and ipsilateral Taichong and Hegu, simultaneous oral placebo for 40 days. The ESC group received oral escitalopram oxalate tablets 10mg to 20mg for 40 days, plus 30 sessions of sham electroacupuncture. The effectiveness of the treatment was evaluated by the Hamilton Depression Scale (HAMD-17), Self-Depression Scale (SDS), Modified Barthel Index Score (MBI), and the serum levels of IL-1β, IL-6, IL-10, TNF-α, and INF-γ. Results: There was no statistically significant difference in the baseline data, or parameter levels between the two groups before the intervention (P >0.05). After treatment, HAMD-17 and SDS scores continued to decrease and MBI scores continued to increase in both groups. The differences were statistically significant at the 6th week vs baseline, the 10th vs baseline, and the 10th vs the 6th (all P <0.001). The differences in HAMD-17, SDS, and MBI scores between the two groups at the 6th were not statistically significant (P=0.110, 0.115, 0.516, respectively); HAMD-17 scores and SDS scores in the EA group were lower than those in the ESC group at the 10th, and the differences were statistically significant (P=0.002,0.026, respectively). In the 6th week, the serum levels of IL-1β, IL-6, TNF-α, and INF-γ were significantly lower in both groups vs baseline, while IL-10 was significantly higher. The difference between the pre-and post-intervention intra-group comparisons was statistically significant (P <0.001), and the difference between the inter-group comparisons was not statistically significant (P >0.05). No serious adverse events occurred throughout the trial. Both therapies could safely and effectively improve HAMD-17, SDS, and MBI scores and modulate neuroinflammatory responses for PSD. After the treatment stopped, some parameters were better in the EA group than ESC group in a short time. Conclusion: Electroacupuncture is an effective, alternative to escitalopram for the treatment of mild-to-moderate PSD.